Preliminary evaluation of a highly automated instrument for the selection of CD34+ cells from mobilized peripheral blood stem cell concentrates. Issue 2 (27th October 2015) - Stroncek, David F.; Tran, Minh; Frodigh, Sue Ellen; David‐Ocampo, Virginia; Ren, Jiaqiang; Larochelle, Andre; Sheikh, Virginia; Sereti, Irini; Miller, Jeffery L.; Longin, Kevin; Sabatino, Marianna
Abstract : BACKGROUND: Cell selection is an important part of manufacturing cellular therapies. A new highly automated instrument, the CliniMACS Prodigy (Miltenyi Biotec), was evaluated for the selection of CD34+ cells from mobilized peripheral blood stem cell (PBSC) concentrates using monoclonal antibodies conjugated to paramagnetic particles. STUDY DESIGN AND METHODS: PBSCs were collected by apheresis from 36 healthy subjects given granulocyte–colony‐stimulating factor (G‐CSF) or G‐CSF plus plerixafor. CD34+ cells from 11 PBSC concentrates were isolated with the automated CliniMACS Prodigy and 25 with the semiautomated CliniMACS Plus Instrument. RESULTS: The proportion of CD34+ cells in the selected products obtained with the two instruments was similar: 93.6 ± 2.6% for the automated and 95.7 ± 3.3% for the semiautomated instrument (p > 0.05). The recovery of CD34+ cells from PBSC concentrates was less for the automated than the semiautomated instrument (51.4 ± 8.2% vs. 65.1 ± 15.7%; p = 0.019). The selected products from both instruments contained few and similar quantities of platelets (PLTs) and red blood cells. The depletion of CD3+ cells was less with the automated instrument (4.34 ± 0.2 log depletion vs. 5.20 ± 0.35 log depletion; p < 1 × 10 −6 ). Removal of PLTs from PBSC concentrates by washing was associated with better CD34+ cell recovery. We explored the reasons for lower CD34+ cell recovery by the Prodigy and found that the nonselected cells for the Prodigy contained more PLTs than those for the CliniMACS Plus. CONCLUSIONS: CD34+ cells can be effectively selected from mobilized PBSC concentrates with the CliniMAC Prodigy, but the recovery of CD34+ cells and depletion of CD3+ cells was lower than with the semiautomated CliniMACS Plus Instrument.